2020
DOI: 10.1101/2020.06.22.165134
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-throughput 5’P sequencing enables the study of degradation-associated ribosome stalls

Abstract: RNA degradation is critical for gene expression and mRNA quality control. mRNA degradation is intimately connected to the translation process up to the degree that 5'-3' co-translational mRNA degradation can be used as a proxy for ribosome dynamics. Here we present an improved high-throughput 5'P RNA sequencing method (HT-5Pseq). HT-5Pseq is easy, scalable and uses affordable duplex-specific nuclease based rRNA depletion. We investigate in vivo ribosome stalls in Saccharomyces cerevisiae and Schizosaccharomyce… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 46 publications
(82 reference statements)
4
8
0
Order By: Relevance
“…This effect was not dependent on genotype (early flowering, flc-3, or late flowering, FLC) or the tissue under study (cotyledons from day 6, apices from days 9 and 11, and leaves from days 14, 23, 32 and 33) ( Figure 5A). Increased termination stall during A. thaliana development is in line with previously observed reduction in polysome associated mRNAs (45), and the increased ribosome termination stalls that we previously described in budding yeast during limited nutrient conditions or stationary phase (3,8). Interestingly, apices showed subtle preference for 5'P counts 17nt upstream from the stop codon, as opposed to the general -16 nt preference in the other samples ( Figure 5A, Figure S3E).…”
Section: Contribution Of Ribosome Stalling and Eif5a Depletion To Ribsupporting
confidence: 91%
See 4 more Smart Citations
“…This effect was not dependent on genotype (early flowering, flc-3, or late flowering, FLC) or the tissue under study (cotyledons from day 6, apices from days 9 and 11, and leaves from days 14, 23, 32 and 33) ( Figure 5A). Increased termination stall during A. thaliana development is in line with previously observed reduction in polysome associated mRNAs (45), and the increased ribosome termination stalls that we previously described in budding yeast during limited nutrient conditions or stationary phase (3,8). Interestingly, apices showed subtle preference for 5'P counts 17nt upstream from the stop codon, as opposed to the general -16 nt preference in the other samples ( Figure 5A, Figure S3E).…”
Section: Contribution Of Ribosome Stalling and Eif5a Depletion To Ribsupporting
confidence: 91%
“…Although initially considered independent events, multiple evidence has now demonstrated that translation and mRNA decay are interconnected processes and that co-translational mRNA degradation is a general phenomenon (2)(3)(4)(5). The interaction between the translation and decay machinery occurs so close that the positions of 5'P co-translational mRNA degradation intermediates can be used as a proxy for ribosome dynamics, as we and others have shown in yeast (6)(7)(8) and plants (4,9,10). In particular, XRN1driven 5'-3' mRNA degradation is linked to the movement of the last translating ribosome allowing to obtain an in vivo footprint of the ribosome position.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations